Prosocial practices of mortality interpretation: racial-anthropological and sociocultural aspects - I. E. Levchenko; O. A. Polyushkevich (Acta Biomedica Scientifica, 2022)
Background. The perception of mortality is consistent with pro-social practices that determine social development. Combining the tools of racial-anthropological and sociocultural approaches makes it possible to identify the universal characteristics and interpretations of mortality in modern society.Aim of the study: identification of pro-social practices and specific interpretations of mortality through the unity and opposition of the racial-anthropological and socio-cultural aspects of social reproduction.Methods. A mass survey of the population of the Russian Federation (n = 1200) aged 18 to 65 living in different regions of the Russian Federation (55 % women, 45 % men) was conducted. A content analysis of media and Internet materials was performed to fix estimates of death and mortality in the Russian Federation over the past five years (n = 1456) in publications or informational messages.Results. The impact of the anthropological and sociocultural aspects was manifested through how and what people think about death, as well as how death exists in a social context. The personal-psychological context of the perception of death and mortality, the memorialization of places of death and the socio-economic and cultural-organizational practices of death determine the personal and social forms of interpretation of mortality. Content analysis of media materials and the Internet revealed a significant increase in the volume and frequency of attention to death and mortality. This is due to the situation with the pandemic, as well as the actualization of the fears of Russians about their well-being and social conditions for accepting and assessing death and mortality.Conclusion. Prosocial practices, being a personal experience of experiencing and a tool for social inclusion in acceptable norms of behavior, influence sociocultural meanings and anthropological conditions for the perception of mortality.